2007
DOI: 10.21273/hortsci.42.3.508
|View full text |Cite
|
Sign up to set email alerts
|

Floral Competence of Primocane-fruiting Blackberries Prime-Jan and Prime-Jim Grown at Three Temperature Regimens

Abstract: We investigated the responses of staminate and pistillate floral components of Prime-Jan and Prime-Jim primocane-fruiting blackberry (Rubus L. subgenus Rubus Watson) to three different growth chamber temperature regimens, 35.0/23.9 °C (HT), 29.4/18.3 °C (MT), and 23.9/12.8 °C (LT). Temperature was negatively related to flower size, and morphologically abnormal floral structures were evident in 41% and 98% of the MT- and HT-grown plants, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The sides were kept down in the early spring of this study for the kale and spinach season, which may have caused a negative effect on blackberry yield. In other studies with primocane fruiting blackberry, flowers of high tunnel cultivated plants exhibited decreases in pollen competence of up to 75% due to high temperatures (Stanton et al, 2007). The possible temperature-induced low pollen competence may be responsible for the observed low drupelet density of some berries in this study.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The sides were kept down in the early spring of this study for the kale and spinach season, which may have caused a negative effect on blackberry yield. In other studies with primocane fruiting blackberry, flowers of high tunnel cultivated plants exhibited decreases in pollen competence of up to 75% due to high temperatures (Stanton et al, 2007). The possible temperature-induced low pollen competence may be responsible for the observed low drupelet density of some berries in this study.…”
Section: Resultssupporting
confidence: 54%
“…Blackberry has a lethal minimum temperature of 0°F, after which canes will exhibit damage and be less fruitful (Yao, 2018). To be fruitful, blackberry needs a dormancy period with 300 to 900 chilling hours spent in temperatures below 45°F (Stanton et al, 2007). Blackberry canes can live for 15 years and are productive for 9 years, depending on cultivar and cultivation practices (Takeda et al, 2002).…”
mentioning
confidence: 99%
“…4). Furthermore, ovule viability and receptivity to pollen grains has been shown to decline with exposure to high temperatures (29 to 35°C ; Stanton et al, 2007). Drake and Clark (2003) reported that bloom time temperatures of 36°C resulted in small, crumbly fruit from tipped treatments in 'Prime-Jan' and 'Prime-Jim'.…”
Section: Resultsmentioning
confidence: 99%
“…Genotypes of annual-fruiting blackberry are being grown in evaluation trials in many production regions. Cultivars that are less sensitive to high temperature effects on fruit set (Stanton et al, 2007), sun damage of fruit, can be manipulated to fruit during high-value market seasons, and are thornless are desired.…”
Section: Erectmentioning
confidence: 99%